Short communication. First report in Cuba of bovine coronavirus detection in a winter dysentery outbreak - Barrera Valle, M.=700 1 Rodriguez Batista, E.; Betancourt Martell, A.; Frias Lepuroux, M.T.; Brandao, P.
(Es, En)
ilus., 10 ref.
Keywords: DIAGNOSTICO; DIARREA; VIROSIS; GANADO BOVINO; ENSAYO BIOLOGICO; PCR; INFECCION; ESPAÑA; ENSAYOS; RT-PCR; INFECCION POR BCoV